Review of emergency obstetric care interventions in health facilities in the Upper East Region of Ghana: a questionnaire survey - Minerva Kyei-Onanjiri; Mary Carolan-Olah; John Koku Awoonor-Williams; Terence V. McCann (BMC, 2018)
Abstract Background Maternal morbidity and mortality is most prevalent in resource-poor settings such as sub-Saharan Africa and southern Asia. In sub-Saharan Africa, Ghana is one of the countries still facing particular challenges in reducing its maternal morbidity and mortality. Access to emergency obstetric care (EmOC) interventions has been identified as a means of improving maternal health outcomes. Assessing the range of interventions provided in health facilities is, therefore, important in determining capacity to treat obstetric emergencies. The aim of this study was to examine the availability of emergency obstetric care interventions in the Upper East Region of Ghana. Methods A cross-sectional survey of 120 health facilities was undertaken. Status of emergency obstetric care was assessed through an interviewer administered questionnaire to directors/in-charge officers of maternity care units in selected facilities. Data were analysed using descriptive statistics. Results Eighty per cent of health facilities did not meet the criteria for provision of emergency obstetric care. Comparatively, private health facilities generally provided EmOC interventions less frequently than public health facilities. Other challenges identified include inadequate skill mix of maternity health personnel, poor referral processes, a lack of reliable communication systems and poor emergency transport systems. Conclusion Multiple factors combine to limit women's access to a range of essential maternal health services. The availability of EmOC interventions was found to be low across the region; however, EmOC facilities could be increased by nearly one-third through modest investments in some existing facilities. Also, the key challenges identified in this study can be improved by enhancing pre-existing health system structures such as Community-based Health Planning and Services (CHPS), training more midwifery personnel, strengthening in-service training and implementation of referral audits as part of health service monitoring. Gaps in availability of EmOC interventions, skilled personnel and referral processes must be tackled in order to improve obstetric outcomes.